TUỔI ĐẲNG THỜI Sm/Nd ĐÁ SIÊU MAFIC TRONG ĐỚI XIẾT TRƯỢT SÔNG HỒNG VÀ Ý NGHĨ ĐỊA ĐỘNG LỰC - Vượng, Nguyễn Văn; HANSEN, BENT; WEMMER, KLAUS; Thắng, Tạ Trọng; Chương, Mai Hồng (Vietnam Journal of Earth Sciences, 2017)
The Con Voi range is the southeastward continuity of the tertiary Red River Ailao Shan shear zone. The range consists of high-grade metamorphic and strongly deformed rocks with amphibolitic lenses, ultramafic-mafic bodies intercalated inside the shear zone. The whole range was sheared and metamorphosed during it’s sinitral displacement. However, Sm/Nd isochron dating one ultramafic body captured within the shear zone yields a protolith age of 490 My, with initialratio of 143Ndf1 44Nd = 0.511742 and t:!;J(1 = -5.19,t:(/" = -8.32. This result suggests a long and multiphasal tectonics of the Red River-Ailao Shan shear zone. On the other hand, it shows thecapacity of "seeing through" the thermotectonic events overprinted upon the older structures of theSm/Nd isochron dating method.